Correlation of diabetic retinopathy with thyroid status - Lalit Sachdeva; Neha Srivastava; Vishal Yadav; Anil Kumar Srivastava (Journal of Clinical Ophthalmology and Research, 2023)
Background: Several studies have demonstrated a correlation between subclinical hypothyroidism (SCH) and diabetic retinopathy (DR) with conflicting results. The study is aimed to find out the correlation and severity of DR with thyroid status. Materials and Methods: A cross-sectional study was conducted taking up 59 patients of DR and categorized them according to the severity of DR as per early treatment DR study classification. Thyroid stimulating hormone (TSH), free thyroxine (FT4), and FT3 concentration were measured in all 59 patients. Patients with normal TSH and FT4 values are euthyroid patients and those with normal FT4 but TSH >4.12 mIU/L is considered having SCH and those with FT4 <0.93 ng/dL and TSH >4.12 mIU/L are considered having hypothyroidism. The severity of DR is compared between the euthyroid, subclinical hypothyroid, and hypothyroid groups. Results: Out of the 59 patients included in the study, 23 (38.98%) were females and 36 (61.01%) were males. Out of 59 cases of DR, 51 (86.44) cases were diagnosed with nonproliferative DR (NPDR) and 8 (13.56%) were diagnosed with PDR. Fifteen had thyroid dysfunction, SCH were seen in 13 patients, two patients had hypothyroidism, and 44 had euthyroid. Fifty-one patients of NPDR and SCH were seen in seven patients, and hypothyroid was present in two patients. In eight patients of PDR, six had SCH. Conclusions: In the present study, the prevalence of SCH among the patients of DR with type 2 diabetes mellitus (DM) was found to be 20.33%. The prevalence of severe NPDR and PDR was higher in patients with SCH compared to euthyroid patients. Therefore, SCH is associated with the severity of DR.